The Labour Party and the Nursing Profession - MacDonald, James Ramsay, 1866-1937 (London : The Labour Party (London : Co-operative Print. Society Ltd.), 1927)
1927 1927 1920s 40 pages 15 ACCESS TO A DOCTOR. The usual procedure for a nurse feeling ill is to report to a sister or the matron, who sends her to the doctor. One of the doctors on the staff is usually the panel doctor for the nurse concerned under the National Health Insurance Act. One hospital reported that the nurse could go to her own doctor upon request. In a London hospital "a consultant from each medical service is appointed to be responsible for the health of nurses and attend at regular and frequent times, but all nurses can consult any member of the staff whenever they want to." Another remarks that a "medical officer especially appointed for the purpose attends daily at the nurses' home." UNEMPLOYMENT. There seems to be no unemployment problem among nurses. There is such a scarcity of them that the demand is much greater than the supply. Most hospitals like to fill vacancies in the post of sister from their own nurses. One Poor Law infirmary reported that all nurses have the opportunity of remaining after obtaining their certificates for a minimum of six months as staff nurses. One hospital says that "requests for names of nurses leaving are more numerous than can be met," and another that "each nurse could be placed three times over." SUPERANNUATION BENEFITS OR PENSIONS. The great majority of the general hospitals have no superannuation or pension scheme. Individual nurses (over 3,000) are pensioned through the Royal British Pension Fund for Nurses. Examples showing exceptions are given below : — HOSPITAL 1.— A non-contributory pension scheme. The nurses may retire at 50 and must at 60. HOSPITAL 2.— A pension scheme for all in permanent service. Age of retirement being from 55 to 60. HOSPITAL 3.— A non-contributory pension after 20 years' service of not less than £60 a year. HOSPITAL 4.— Pensions granted at 55 or after 25 years' service. All the nurses in the Poor Law infirmaries come under the Poor Law Officers' Superannuation Acts of 1864-97. Under this scheme 2 per cent. is deducted from salary and emoluments to form a pension fund. After ten years' service a nurse is entitled to a pension of one-sixtieth of her average salary during the previous five years for each year of service, with a maximum of forty-sixtieths. A nurse may retire at 60 if medically unfit and may be obliged to retire at 65 if the guardians think it would be expedient in the interests of the public service. One Poor Law infirmary reported that most of the nurses contract out, and under the Act they are not allowed to rejoin. Another reported that four nurses were pensioned in the last two years — one at 72, another 71, another 61, and another 59. This advanced age of retirement specified by the Act is, as one matron expressed it, "absolutely terrible." She goes on to say: "The age of retirement for people leading a strenuous life amongst unhealthy people who are depressed ought to be much less than 65 as when one reaches 65 there are not many years left to enjoy freedom. It ought to be 55 not 65 if the nurse wishes to retire, and nurses who have been silly enough to contract out of the superannuation scheme ought to have a chance of rejoining and paying up any arrears, because nurses often think they'll marry and not require superannuation, and they commence nursing and get absorbed in the work, and alas, there's nothing left for old age." 126/TG/RES/X/1036A/14